A Network Pharmacology-Based Strategy for Unveiling the Mechanisms of Tripterygium Wilfordii Hook F against Diabetic Kidney Disease. (20th November 2020) - Wang, Yuyang; Liu, Tongtong; Ma, Fang; Lu, Xiaoguang; Mao, Huimin; Zhou, Weie; Yang, Liping; Li, Ping; Zhan, Yongli
Abstract : Background . Diabetic kidney disease (DKD) poses a major public-health burden globally. Tripterygium wilfordii Hook F (TwHF) is a widely employed herbal medicine in decreasing albuminuria among diabetic patients. However, a holistic network pharmacology strategy to investigate the active components and therapeutic mechanism underlying DKD is still unavailable. Methods . We collected TwHF ingredients and their targets by traditional Chinese Medicine databases (TCMSP). Then, we obtained DKD targets from GeneCards and OMIM and collected and analyzed TwHF-DKD common targets using the STRING database. Protein-protein interaction (PPI) network was established by Cytoscape and analyzed by MCODE plugin to get clusters. In addition, the cytoHubba software was used to identify hub genes. Finally, all the targets of clusters were subjected for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses via DAVID. Results . A total of 51 active ingredients in TwHF were identified and hit by 88 potential targets related to DKD. Compounds correspond to more targets include kaempferol, beta-sitosterol, stigmasterol, and Triptoditerpenic acid B, which appeared to be high-potential compounds. Genes with higher degree including VEGFA, PTGS2, JUN, MAPK8, and HSP90AA1 are hub genes of TwHF against DKD, which are involved in inflammation, insulin resistance, and lipid homeostasis. Kaempferol and VEGFA were represented as the uppermost active ingredient and core gene of TwHF in treating DKD, respectively. DAVID results indicated that TwHF may play a role in treating DKD through AGE-RAGE signaling pathway, IL-17 signaling pathway, TNF signaling pathway, insulin resistance, and calcium signaling pathway (P < 0.05 ). Conclusion . Kaempferol and VEGFA were represented as the uppermost active ingredient and core gene of TwHF in treating DKD, respectively. The key mechanisms of TwHF against DKD might be involved in the reduction of renal inflammation by downregulating VEGFA.